What factors affect Beijing residents' contracts with family doctors? A comparative study of Beijing's urban and suburban areas - Bo Lv; Chengsen Cui; Xingmiao Feng; Kai Meng (Frontiers Media S.A., 2023)
ObjectiveTo improve the health of residents and promote hierarchical diagnosis and treatment to achieve an orderly pattern of medical treatment, Beijing implemented family doctor contract services (FDCSs) in 2011. The aims of this study were to analyze the current status of Beijing residents' contracts with family doctors (FDs), compare the differences in contracting between urban and suburban residents, and explore the factors that affect residents' contract behavior.MethodsFrom August 2020 to October 2020, a stratified sampling method was adopted to select residents from community health centers (CHCs) in districts D (urban area) and S (suburb) of Beijing to conduct a questionnaire survey. Chi-square tests, rank sum tests and logistic regression analyzes were used to analyze the current status and influencing factors of residents' contracting with FDs.ResultsA total of 4,113 valid questionnaires were included in the final analysis. District D was rich in medical resources, and the FD contract rate of residents there (93.09%) was significantly higher than that of residents in district S (78.06%; p < 0.05). Residents' district (OR = 1.55, 95% CI = 1.18-2.05), understanding of FDCS policies (OR = 4.13, 95% CI = 3.63-4.69), preferred medical institutions (OR = 0.58, 95% CI = 0.42-0.79 for tertiary hospitals in the district; OR = 0.36, 95% CI = 0.22-0.59 for urban medical institutions in Beijing), age, education level, average annual medical expenses and medical insurance type were factors that influenced residents' contracts with FDs (p < 0.05).ConclusionThis study shows that residents who are located in districts with rich medical resources, prefer CHCs as their first choice, have a better understanding of FDCS policies, and are more inclined to contract with FDs than other residents. It is recommended that the number and quality of FDs in suburban areas be increased and that medical staff strengthen publicity about FDCSs and actively encourage residents to contract with FDs.